Physico-chemical studies on the enzymatic coagulation of milk - B. Tarodo de la Fuente; C. Alais (CHIMIA)
In a recent publication that appeared in this review Alais outlined our present knowledge of κ- and whole casein, of chymosin and other coagulating enzymes. He also described the action of chymosin (rennin) on the casein. In this paper we give a review of what is known on the alterations and the stages of milk and casein following the reaction of the enzyme. Thus we shall consider the actual coagulation or the secondary phase, the paracaseinate gel syneresis and the different methods of studying the two phenomena.